Simultaneous plasma and genital pharmacokinetics and pharmacodynamics of atazanavir and efavirenz in HIV‐infected women starting therapy. (30th March 2015) - Neely, Michael; Louie, Stan; Xu, Jiaao; Anthony, Patricia; Thuvamontolrat, Kasalyn; Mordwinkin, Nicholas; Kovacs, Andrea
Abstract Few studies have characterized longitudinal female plasma and genital antiretroviral pharmacokinetics and pharmacodynamics. Among 20 regimen‐naive HIV‐infected adult women initiating atazanavir‐based therapy (n = 9) or efavirenz‐based therapy (n = 11), we measured blood CD4+ T lymphocytes, and paired plasma and genital HIV RNA and atazanavir or efavirenz 2 days before starting therapy and 2, 4, 7, 10, 21, 28, 60, 120, and 180 days after. The mean (range) log10 baseline plasma viral load was 4.89 copies/mL (2.64–6.09 copies/mL), and genital was3.30 (1.60–5.00). In the atazanavir and efavirenz groups, mean (SD) days to a 50% decrease in plasma viral load was 8.2 (4.9) versus 9.3 (7.4), P = .7, and in the genital tract it was 7.3 (3.5) versus 9.3 (7.7), P = .5. The median (interquartile range) plasma:genital concentration ratio for atazanavir was 0.11 (0.001–0.46) versus 0.34 (0.05–1.30) for efavirenz, P = .5. Average plasma efavirenz or atazanavir concentrations over time did not affect virologic response. Blood CD4+ percentages increased by +2.3 (P = .06) and +3.0 (P = .003) for every 1 mg/L increase in average plasma and genital drug concentration, respectively. Plasma and genital viral pharmacodynamics were similar between the groups and independent of average concentrations, but blood CD4+ response was related in particular to genital extravascular drug concentrations.